Inapplicability of fractional moving blood volume technique to standardize Virtual Organ Computer-aided AnaLysis indices for quantified three-dimensional power Doppler. - Welsh, A; Collins, S; Stevenson, G; Noble, J; Impey, L (2012)
OBJECTIVE: To determine whether the technique of fractional moving blood volume (FMBV) is applicable to Virtual Organ Computer-aided AnaLysis II (VOCAL II™)-based indices to quantify three-dimensional power Doppler ultrasound (3D-PDU) by investigating the effect of gain level on the indices measured at a possible reference point for standardization. METHODS: Ten women with singleton pregnancy between 33+3 and 37+5 weeks' gestation were recruited. The optimal position for 3D acquisition of cord insertion into the placenta was identified and static 3D-PDU volumes were acquired using consistent machine configurations. Without moving the probe or the participant changing position, successive 3D volumes were stored at -3, -5, -7 and -9 dB and at the individualized sub-noise gain (SNG) level. Volumes were excluded if flash artifact was present, in which case all five volumes were reacquired. Using 4D View software, the cord insertion was magnified and the smallest sphere possible was used to measure vascularization index (VI), flow index (FI) and vascularization flow index (VFI). The associations between VOCAL indices and gain level were assessed using Pearson's correlation coefficient. RESULTS: VOCAL indices for cord insertion correlated poorly with gain level, whether fundamental or relative to SNG level (R(2) = 0.07 and 0.04, respectively). VI was consistently 100% and mean FI and VFI were 99.5 (SD, 0.57), with all values > 97 irrespective of gain level. CONCLUSIONS: Whilst previous work has shown that gain correlates well with placental tissue VOCAL indices, the correlation between gain level and VOCAL indices in an area of 100% vascularity at the cord insertion is poor. Regions of 100% vascularity appear to be artificially assigned a value approaching 100% for all VOCAL indices irrespective of gain level. This precludes using the technique of VOCAL indices from large vessels to standardize power Doppler measurements and the FMBV index is therefore not applicable to image analysis using VOCAL.